High-performance particulate matter including nanoscale particle removal by a self-powered air filter - Zhang, Guo-Hao; Zhu, Qiu-Hong; Zhang, Lei; Yong, Fang; Zhang, Zhang; Wang, Shuang-Long; Wang, You; He, Ling; Tao, Guo-Hong (Nature communications, 2020)
Particulate matter (PM) pollutants, including nanoscale particles (NPs), have been considered serious threats to public health. In this work, a self-powered air filter that can be used in high-efficiency removal of PM, including NPs, is presented. An ionic liquid–polymer (ILP) composite is irregularly distributed onto a sponge network to form an ILP@MF filter. Enabled by its unique electrochemical properties, the ILP@MF filter can remove PM 2.5 and PM 10 with high efficiencies of 99.59% and 99.75%, respectively, after applying a low voltage. More importantly, the charged ILP@MF filter realizes a superior removal for NPs with an efficiency of 93.77%. A micro-button lithium cell or silicon-based solar panel is employed as a power supply platform to fabricate a portable and self-powered face mask, which exhibits excellent efficacy in particulate removal compared to commercial masks. This work shows a great promise for high-performance purification devices and facile mask production to remove particulate pollutants. Particulate matter (PM) pollutants have been considered serious threats to public health but effective removal of nanoscale particles (NPs) by filter materials is challenging. Here, the authors fabricate an ionic liquid based self-powered air filter that can be used in high-efficiency removal of PM, including NPs.